2003
DOI: 10.5210/fm.v8i1.1019
|View full text |Cite
|
Sign up to set email alerts
|

The Institutional Design of Open Source Programming: Implications for Addressing Complex Public Policy and Management Problems

Abstract: Recently, an exciting approach to solving complex problems has evolved out of computer science, called Open Source programming. In open source software development settings, programmers freely share their intellectual property ? their readable programming source code ? over the Internet. Some open source endeavors have resulted in very complex, high-quality software products, of which the best-known are the Linux operating system and the Apache Web server. A great advantage of an Internet-based open source app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 0 publications
0
33
0
1
Order By: Relevance
“…At that point it is important to reach programmers who think along with this new initiative. Motivation, "the kernel," and a modular design are three important components of this stage of an OSS project (Schweik and Semenov, 2003). Even if there is an increasing number of studies that have focused on the motivation of programmers to take part in OSS communities (Hertel et al, 2003), parallel.…”
Section: Organizational Growth and The Emergence Of Informal Forms Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…At that point it is important to reach programmers who think along with this new initiative. Motivation, "the kernel," and a modular design are three important components of this stage of an OSS project (Schweik and Semenov, 2003). Even if there is an increasing number of studies that have focused on the motivation of programmers to take part in OSS communities (Hertel et al, 2003), parallel.…”
Section: Organizational Growth and The Emergence Of Informal Forms Ofmentioning
confidence: 99%
“…For OSS communities, a critical growth stage is reached at the moment they are moving from the project initiation stage to the stage of "going open" (Rasters, 2004, Schweik andSemenov, 2003 (Ouchi, 1979). Organizational life cycle theorists have shown that the internal structure of organization is changing by going through different growth stages (introduction, growth, maturity or decline).…”
Section: Mature Oss Communities and Their Governance Formsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inexperienced volunteer programmers often participate in FOSS projects in order to build their own skills through the reading and writing of code and by being subjected to the peer-review process. Through this participation, they hope to show off their skills, make connections and build a reputation with, in part, the hope of gaining future economic opportunities (Feller and Fitzgerald, 2001;Schweik and Semenov, 2003;Lerner and Tirole, 2005).…”
Section: The Negative Effects Of Institutions?mentioning
confidence: 99%
“…In order to study FOSS institutions and their influence on the success or failure of projects, there are three important attributes that need to be considered: (1) Evolutionary (Schweik and Semenov, 2003;Schweik, 2005) we noted that FOSS projects go through two stages, Initiation and Growth. We define the Initiation Stage as the initial period of time a project goes through where people are collaborating on software code but there has yet to be a public release of this code.…”
Section: Three Important Attributes Of Foss Commonsmentioning
confidence: 99%